2013
DOI: 10.1016/j.bbamcr.2012.11.029
|View full text |Cite
|
Sign up to set email alerts
|

FKBP52 is involved in the regulation of SOCE channels in the human platelets and MEG 01 cells

Abstract: Immunophilins are FK506-binding proteins that have been involved in the regulation of calcium homeostasis, either by modulating Ca(2+) channels located in the plasma membrane or in the rough endoplasmic reticulum (RE). We have investigated whether immunophilins would participate in the regulation of stored-operated Ca(2+) entry (SOCE) in human platelets and MEG 01. Both cell types were loaded with fura-2 for determining cytosolic calcium concentration changes ([Ca(2+)](c)), or stimulated and fixed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Since that, Orai1 expression was observed in the human megakaryocytic cell line MEG-01 [172,173]. Borst et al demonstrated that Orai1 expression is modulated by the serum- and glucocorticoid-inducible kinase 1 (SGK1) [172], a kinase belonging to the AGC family of serine/threonine protein kinases [174,175], that can be regulated by a variety of different triggers, including hormones, thrombin, oxidative stress and growth factors [175].…”
Section: Biogenesis Of Store-operated Calcium Entry During Thrombomentioning
confidence: 99%
“…Since that, Orai1 expression was observed in the human megakaryocytic cell line MEG-01 [172,173]. Borst et al demonstrated that Orai1 expression is modulated by the serum- and glucocorticoid-inducible kinase 1 (SGK1) [172], a kinase belonging to the AGC family of serine/threonine protein kinases [174,175], that can be regulated by a variety of different triggers, including hormones, thrombin, oxidative stress and growth factors [175].…”
Section: Biogenesis Of Store-operated Calcium Entry During Thrombomentioning
confidence: 99%
“…The reduction on Thr-evoked phospho-mTOR in Ser 2448 , which is targeted by Akt, was mostly evidenced in platelets preincubated with Gal Asc, Caf Asc, and Asc despite that the result were not significant regarding the values found in platelet non-treated with the esters. The impaired activation of mTOR upon Thr activation resulting from elevated basal activation levels might explain the reduction in calcium homeostasis and subsequent impaired aggregation in response to the physiological agonist, due to mTOR have been previously evidenced to participate in both signaling pathways in this cell type, as reported by our group and others [20,38,40]. In case of gallic acid, clinical trials using this phytochemical have reported inhibition of mTOR [70], which agree with the negative effect of Gal Asc over Akt-dependent mTOR phosphorylation evoked by Thr in our cell type.…”
Section: Discussionmentioning
confidence: 82%
“…While it has been shown that it participated in store-operated Ca 2+ entry pathways affecting platelet activation and thrombus formation (Rosado and Sage 2001;Lopez et al 2013;Jardin et al 2012;Rosado et al 2002), studies using platelets derived from the Trpc1 knockout mice could not show an effect on either store-operated Ca 2+ entry or platelet function, such as activation, aggregation, hemostasis, and thrombosis (Varga-Szabo et al 2008). …”
Section: Cardiovascular Systemmentioning
confidence: 97%